Patterns of Asthma Medication Use across the Transition to High School. (7th February 2021) - McQuaid, Elizabeth L; Kopel, Sheryl J; Seifer, Ronald; Tackett, Alayna; Farrow, Michael; Koinis-Mitchell, Daphne; Dunsiger, Shira
Abstract: Objective: Adherence to asthma controller medications is suboptimal among adolescents. We evaluated predictors of adherence and longitudinal patterns of medication use between 8th and 10th grade among a sample of youth of diverse race/ethnicity. Methods: Eighth graders with asthma on controller medications ( N  =   62; 40.0% non-Latino white; 23.7% Black; 37.3% Latino; 37.3% female) completed measures of medication beliefs, responsibility for asthma management, and family cohesion. Objective methods tracked medication use longitudinally. Results: Adherence declined during the high school transition, from 48.0% in eighth grade to 34.1% in tenth grade ( F  =   5.35, p < .01). Males had lower adherence ( b = −10.11, SE   =   5.37, p = .02, f 2 = 0.11), as did Latino youth ( b = −12.21, SE   =   8.23, p = .03, f 2 = 0.12). Family cohesion was associated with higher adherence ( b  =   4.38, SE   =   1.98, p = .04, f 2 = 0.06). Latent class models (LCMs) suggested a three-class model of longitudinal adherence patterns. This included low, declining adherence (Class 1 = 29%; higher proportion male, p = .02), high, sustained adherence (Class 2 = 26%, high family cohesion, p = .05, higher proportion female, p = .02), and low, sustained adherence (Class 3 = 45%; higher proportion Latino, p = .05, higher proportion male, p = .02). Conclusions: Asthma medication adherence declined between 8th and 10th grade. LCMs indicated some youth have stable patterns of adherence (high or low), whereas others demonstrate declines. Gender differences were observed, and family cohesion was associated with higher, sustained adherence. Interventions building on family resources and targeting the barriers adolescents face are necessary to improve asthma management during this vulnerable period.